2021
DOI: 10.14245/ns.2142016.008
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Minimally Invasive Spine Surgery With Midline Cortical Bone Trajectory Screw Fixation for Lumbar Degenerative Disease in a Retrospective Study of 200 Patients

Abstract: Objective: Midline lumbar interbody fusion is performed for treatment of various lumbar degenerative diseases, with good clinical outcomes and few complications. However, there are no large-scale or long-term studies regarding midline lumbar interbody fusion. Therefore, the purpose of this study was to evaluate the clinical results of midline lumbar interbody fusion and to compare the results according to surgical level. Methods: Between January 2013 and December 2015, 200 patients with lumbar degenerative dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…No significant complications were observed in any patient during long‐term follow‐up. However, previous studies have identified some CBT screw‐related complications, such as screw fall‐off, pedicle fractures, and pseudo‐joint formation 18 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant complications were observed in any patient during long‐term follow‐up. However, previous studies have identified some CBT screw‐related complications, such as screw fall‐off, pedicle fractures, and pseudo‐joint formation 18 …”
Section: Discussionmentioning
confidence: 99%
“…However, previous studies have identified some CBT screw‐related complications, such as screw fall‐off, pedicle fractures, and pseudo‐joint formation. 18 …”
Section: Discussionmentioning
confidence: 99%
“…Меньшие длительность операции, объем кровопотери и мышечной травмы при процедуре MIDLIF способствуют быстрой активизации пациентов, что особенно важно при остеопорозе. При более длительном наблюдении (в течение трех лет) после поясничного спондилодеза с MIDLIF у пациентов с остеопорозом общая частота стабильного костного блока достигает 90,5 % и значимо улучшается качество жизни [26] дом предотвращения расшатывания и инструментальных осложнений [27]. В неконтролируемых ретро-и проспективных исследованиях использование ПММА с канюлированными винтами у пациентов с остеопорозом для выполнения транспедикулярной фиксации в сочетании с заднелатеральным или межтеловым спондилодезом практически исключает вероятность расшатывания винтов и в подавляющем большинстве случаев значимо улучшает клинические исходы [28][29][30][31][32].…”
Section: результатыunclassified
“…The adaption of CBT has demonstrated feasibility and effectiveness in short-segment lumbar fusion surgery. 25,[27][28][29] According to biomechanical studies, the CBT had up to a 30% increase of pullout strength compared to the conventional pedicle trajectory. 26,30 Since CBT potentially improves bone-to-screw osteointegration and reinforces the screw purchase to decrease screw loosening or breakage, it might be a reasonable innovation to adapt CBT for DS in the management of lumbar instability.…”
Section: Introductionmentioning
confidence: 99%